PELATIHAN KEWIRAUSAHAAN DAN MANAJEMEN USAHA BAGI MASYARAKAT DESA DALAM UPAYA PENGUATAN EKONOMI KREATIF DI KELURAHAN MEKARSARI KECAMATAN PULO MERAK KOTA CILEGON - Lestari, Dini Martinda; Kusumawati, Nugrahini; Febrianti, Sindi (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
This community service activity aims to increase the creative economic independence of village communities in Mekarsari Pulo Merak Village, Cilegon City. The main focus of the activity is entrepreneurship and business management training, where participants are involved in a series of workshops, practical sessions and intensive mentoring. The main objective of the activity is to encourage the development of local creative economic potential and increase the competitiveness of micro and small businesses. Through an interactive approach, training participants are given an in-depth understanding of the basic concepts of entrepreneurship, business management, and marketing strategies that are relevant to the characteristics of Pulo Merak village. The evaluation results showed a significant increase in business skills, market understanding, and utilization of local resources among participants. In strengthening the creative economy, this activity succeeded in creating a participatory environment that stimulated collaboration between village communities. In addition, this training encourages the development of creative products and services that are sustainable and take into account aspects of environmental sustainability. It is hoped that the results of this activity can make a positive contribution to increasing community income, diversifying the local economy, and strengthening the active role of the community in managing and developing creative economic potential in Mekarsari Pulo Merak Village.